2012
DOI: 10.1186/2193-1801-1-39
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of body mass index and its change on the risk of breast cancer by molecular subtype: A case-control study in Japanese women

Abstract: Body mass index (BMI) is an independent risk factor for luminal-type breast cancer in Western populations. However, it is unclear whether the impact of BMI differs according to breast cancer subtype in Japanese populations. We conducted a case-control study with 715 cases and 1430 age-and menopausal status-matched controls to evaluate the associations of BMI and its change (from age 20 years to the current age) with breast cancer risk. We applied conditional logistic regression models to estimate odds ratios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 40 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…However this requires further study to fully understand underlying mechanistic factors. Many previous studies demonstrated that the association between BMI and risk of postmenopausal breast cancer is stronger for ER-positive breast cancer than ER-negative breast cancer (Feigelson et al 2006;Suzuki et al 2011;Sueta et al 2012). However some previous studies demonstrated that premenopausal ER-negative breast cancer patients were more likely to be overweight and/or obese at diagnosis compared with ER-positive breast cancer patients (Millikan et al 2008;Kwan et al 2009).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However this requires further study to fully understand underlying mechanistic factors. Many previous studies demonstrated that the association between BMI and risk of postmenopausal breast cancer is stronger for ER-positive breast cancer than ER-negative breast cancer (Feigelson et al 2006;Suzuki et al 2011;Sueta et al 2012). However some previous studies demonstrated that premenopausal ER-negative breast cancer patients were more likely to be overweight and/or obese at diagnosis compared with ER-positive breast cancer patients (Millikan et al 2008;Kwan et al 2009).…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, we examined the correlation between BMI and breast cancer of both premenopausal and postmenopausal women. To try and develop some mechanistic insight, we examined interactions between BMI and expression of estrogen receptor (ER), as these have been previously suggested to be associated in breast cancer patients (Feigelson et al 2006;Millikan et al 2008;Kwan et al 2009;Suzuki et al 2011;Sueta et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Data from large prospective and case-control studies conducted in Shanghai, China, Japan, Korea, Taiwan, Singapore, and Thailand suggest that women with higher body mass indices (BMI) have a 1.5-to 2.0-fold higher risk of breast cancer compared to women with a normal BMI Shu et al, 2001;Li et al, 2006;Wu et al, 2006b;Jee et al, 2008; Suzuki et al, 2013). Moreover, higher BMI has been associated with a higher risk of ER+/PR+ and/or luminal type cancer among Chinese and Japanese women (Yoo et al, 2001;Bao et al, 2011;Sueta et al, 2012;Miyagawa et al, 2013). In studies among Chinese women, overweight/ obesity explained 9% of the variation in postmenopausal breast cancer risk in urban areas and 6% of the variation in breast cancer risk among women in rural areas (Wang et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is an established risk factor for postmenopausal breast cancer among Asian women in eastern Asia and in some countries in south-eastern Asia Shu et al, 2001;Yoo et al, 2001;Li et al, 2006;Jee et al, 2008;Shin et al, 2009;Shi et al, 2010;Bao et al, 2011;Sueta et al, 2012;Kawai et al, 2013;Miyagawa et al, 2013;Sangrajrang et al, 2013;Suzuki et al, 2013). Data from large prospective and case-control studies conducted in Shanghai, China, Japan, Korea, Taiwan, Singapore, and Thailand suggest that women with higher body mass indices (BMI) have a 1.5-to 2.0-fold higher risk of breast cancer compared to women with a normal BMI Shu et al, 2001;Li et al, 2006;Wu et al, 2006b;Jee et al, 2008; Suzuki et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…12,18,20,36 Through previous case-control studies, postmenopausal obesity was shown as a probable risk factor in breast cancer; however, this association was not statistically significant in HR2 HER21 breast cancer. 37,38 Because endogenous estrogen is biologically produced from adipose tissue 39 and is able to inhibit erbB-2 oncogene expression, 40 this carcinogenesis may not be applicable in HR2 HER21 breast cancer. Therefore, the effect of obesity on breast cancer could be lower in HR2 HER21 tumors compared to HR1 HER22 tumors.…”
Section: Discussionmentioning
confidence: 99%